A family study of symbolic learning and synaptic plasticity in autism spectrum disorder - Granerud, Guro; Elvsåshagen, Torbjørn; Arntzen, Erik; Juhasz, Katalin; Emilsen, Nina Merete; Sønderby, Ida Elken; Nærland, Terje; Malt, Eva Albertsen (Frontiers in Human Neuroscience, 2022)
The current study presents a male with autism spectrum disorder (ASD) and a 3q29 deletion, and three healthy first-degree relatives. Our magnetic resonance imaging (MRI) dataset included a healthy control subset. We describe a comprehensive multimodal approach, including equivalence class formation, neurocognitive testing, MRI, and electroencephalography (EEG)-based cortical plasticity, which can provide new insights into socio-communicative and learning impairments and neural underpinnings in ASD. On neurocognitive testing, the participant with ASD showed reduced processing speed, attending behavior, and executive function. He required more training trials in equivalence class training compared with family members and exhibited impaired priming of words compared with priming with images. The proband had smaller intracranial volume and surface area and a larger visual evoked potential (VEP) C1 amplitude than family members and intact long-term potentiation (LTP)-like visual cortex plasticity. Together, these results suggest that 3q29 deletion–related ASD is associated with impaired problem-solving strategies in complex socio-communicative and learning tasks, smaller intracranial and surface area, altered VEP amplitude, and normal LTP-like visual cortex plasticity. Further studies are needed to clarify whether this multimodal approach can be used to identify ASD subgroups with distinctive neurobiological alterations and to uncover mechanisms underlying socio-communicative and learning impairments.